Assessment of Warfarin Therapy Knowledge among Patients with Cardiovascular Disease - Salman, Fatima Kamil; Salman, Muhammed Waheeb (Iraqi National Journal of Nursing Specialties, 2024)
Abstract Objective(s): To assess of knowledge about warfarin therapy in patients with cardiovascular disease and to find out the relationship between patients’ knowledge and sociodemographic characteristics.Methods: A descriptive study was carried out in Ibn Al-Bitar Specialized center for Cardiac Surgery for the period between between  August 3rd, 2022 to May 28th, 2023. A non-probability sampling was used among  (210) patients with cardiovascular disease. The data for study was collected by using a questionnaire was composed of two parts namely: patients sociodemographic characteristics included (7) questions and Warfarin Knowledge scale consists of (24) questions. Data were analyzed using IBM SPSS version 26. Descriptive and inferential data analysis were utilized to summarize the study results.Results: The study indicated that Patients with cardiovascular diseases had knowledge deficits (86.7%) about warfarin Therapy.Conclusions: The study concludes that Patients with cardiovascular diseases had a low level of knowledge regarding warfarin therapy.Recommendation: The study recommend to designing regular and periodic educational programs regarding cardiac medications such as warfarin therapy for increasing patient's knowledge.